NUEVA ESPECIE HERMANA DE ELEUTHERODACTYLUS DE LA CORDILLERA OCCIDENTAL DEL SUROESTE DE COLOMBIA (AMPHIBIA: SALIENTIA: LEPTODACTYLIDAE) - Lynch, John D.; Ruiz-Carranza, Pedro M. (Revista de la Academia Colombiana de Ciencias Exactas, Físicas y Naturales, 1996)
Six new species of frogs are named from the Cordillera Occidental and are associated with previous-known species. A new species from Mistrató, Risaralda, is the nearest relative of E. bellona; these are the only Eleutherodactylus exhibiting cranial co-ossification. A new species from the Serranía de los Paraguas is the nearest relative of E. appendiculatus, a long-snouted species from southern Colombia and Ecuador. Two new species related to E. diaphonus are named from transects in Cauca and Chocó. Two species of the E. sulculus group are named from the Serranía de los Paraguas and the Farallones de Cali. In each case, nearest relatives are distributed allopatrically, often along adjacent transects. Most of the sister species combinations occur in the same altitudinal leve! except that vertical displacement occurs in the E. anomalus group and in the E. loustes group.